HIGHER EDUCATION REFORMING: WORLD TENDENCIES, PROBLEMS, TASKS - Alexander S. Korobtsov (Advanced Engineering Research)
Reasons, problems and tasks of the higher vocational education reforming are considered from the perspective of the world tendencies of the contemporary society development.